Family Socioeconomic Position and Lung Cancer Risk: A Meta-Analysis and a Mendelian Randomization Study - Zou, Xusen; Wang, Runchen; Yang, Zhao; Wang, Qixia; Fu, Wenhai; Huo, Zhenyu; Ge, Fan; Zhong, Ran; Jiang, Yu; Li, Jiangfu; Xiong, Shan; Hong, Wen; et al. (Frontiers in Public Health, 2022)
Background Family socioeconomic position (SEP) in childhood is an important factor to predict some chronic diseases. However, the association between family SEP in childhood and the risk of lung cancer is not clear. Methods A systematic search was performed to explore their relationship. We selected education level, socioeconomic positions of parents and childhood housing conditions to represent an individual family SEP. Hazard ratios (HRs) of lung cancer specific-mortality were synthesized using a random effects model. Two-sample Mendelian randomization (MR) was carried out with summary data from published genome-wide association studies of SEP to assess the possible causal relationship of SEP and risk of lung cancer. Results Through meta-analysis of 13 studies, we observed that to compared with the better SEP, the poorer SEP in the childhood was associated with the increased lung cancer risk in the adulthood (HR: 1.25, 95% CI: 1.10 to 1.43). In addition, the dose-response analysis revealed a positive correlation between the poorer SEP and increased lung cancer risk. Same conclusion was reached in MR [(education level) OR 0.50, 95% CI: 0.39 to 0.63; P: <0.001]. Conclusions This study indicates that poor family socioeconomic position in childhood is causally correlated with lung cancer risk in adulthood.